2019
DOI: 10.5433/1679-0359.2019v40n5p2025
|View full text |Cite
|
Sign up to set email alerts
|

Butter fatty acid composition as a function of soybean oil supplementation and time of milking, and performance of Holstein x Gyr cows fed with chopped elephant grass-based diets

Abstract: The aim of this study was to evaluate the performance of cows fed with a total mixed ration composed of elephant grass and a concentrate containing 0.0% (control), 1.5%, 3.0% or 4.5% soybean oil on a dry matter basis. The effect of milking time (morning versus afternoon) on butter fatty acid composition was also evaluated. Twelve multiparous Holstein x Gyr cows with an average milk production of 18.0±4.6 kg day-1 and 90±25 days in milk were used in a triplicated 4 x 4 Latin square experimental design with 15-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
4
5
0
Order By: Relevance
“…The negative effect of the dietary inclusion of vegetable oils on cow's milk fat content is well documented in the literature (C. G. S. Ribeiro et al, 2018;Lopes et al, 2019;Mahdavi et al, 2019;Rodrigues et al, 2019). Additionally, the current results corroborate Souza et al (2019) Lopes, F. C. F. et al in the productive performance trial.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The negative effect of the dietary inclusion of vegetable oils on cow's milk fat content is well documented in the literature (C. G. S. Ribeiro et al, 2018;Lopes et al, 2019;Mahdavi et al, 2019;Rodrigues et al, 2019). Additionally, the current results corroborate Souza et al (2019) Lopes, F. C. F. et al in the productive performance trial.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of an effect (P>0.05) of SO on DM and NDF ap intake and apparent digestibility (Table 2) corroborates the results of the productive performance trial, presented in our companion paper (Souza et al, 2019). Additionally, the dietary EE content (Table 1) did not exceed 60-70 g kg -1 DM (NRC, 2001), and we employed a strategy of mixing the SO with the concentrate (Lopes et al, 2019). This technique probably avoided the deposition of a layer of oil on the forage particles, which could negatively impair both the adhesion of fibrolytic microbiota and the activity of the enzymes involved in cellulose hydrolysis (Jenkins, 1993).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In Brazil, elephantgrass (Pennisetum purpureum, Schumach) is one of the most important tropical grasses for feeding dairy cows in a cut-and-carry system (Pereira, Morenz, Ledo, & Ferreira, 2016). Studies carried out by our research group have shown that the inclusion of up to 45 g kg -1 vegetable oils rich in linoleic acid (i.e., soybean or sunflower oil) in the DM of chopped elephantgrass-based TMRs improved the nutritional quality of milk (Ribeiro, Lopes, Gama, Morenz, & Rodriguez, 2014;Ribeiro, Lopes, Gama, Rodriguez, & Morenz, 2018; F. C. F. Lopes et al, 2019). Supplementation with these oils promoted an increase in the milk fat content of oleic (cis-9 C18:1), rumenic (cis-9, trans-11 CLA) and vaccenic (trans-11 C18:1) acids, which are beneficial to human health, and a concomitant reduction in hypercholesterolemic lauric (C12:0), myristic (C14:0) and palmitic (C16:0) acids.…”
Section: Introductionmentioning
confidence: 96%